1997
DOI: 10.1111/j.1447-0756.1997.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prolonged Cycles of Chemotherapy on Quality of Life in Gynaecologic Cancer Patients

Abstract: In conclusion, the prescription of prolonged cycles of chemotherapy to patients with gynaecologic cancers does not result in an overall deterioration of QOL. Further more an improvement in subscale and overall QOL was demonstrated in those patients able to attain a complete clinical response (CCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…On the contrary, Carter et al (1997) reported no significant alterations on HRQL when prolonged chemotherapy was administered. Patnaik et al (1998) found that the role of chemotherapy in advanced ovarian cancer was effective in improving quality of life in at least half of the patients, even though only approximately one fourth of patients had an objective response to their disease.…”
Section: Quality Of Life In Ovarian Cancer Patients Choosing To Receimentioning
confidence: 82%
“…On the contrary, Carter et al (1997) reported no significant alterations on HRQL when prolonged chemotherapy was administered. Patnaik et al (1998) found that the role of chemotherapy in advanced ovarian cancer was effective in improving quality of life in at least half of the patients, even though only approximately one fourth of patients had an objective response to their disease.…”
Section: Quality Of Life In Ovarian Cancer Patients Choosing To Receimentioning
confidence: 82%
“…Patients with advanced disease who received chemotherapy for at least 1 year showed a significant deterioration in QOL [13]. In contrast, Carter et al [14] found QOL improvements in patients with ovarian cancer receiving second-or third-line chemotherapy. There was a sustained improvement in emotional and global health status and pain control even in women receiving more than six cycles.…”
mentioning
confidence: 93%
“…Oncological therapies have a profound impact on the quality of life (QOL) of cancer patients resulting in long-term behavioral disruptions and emotional distress [1,2]. Significant effects of irradiation and chemotherapy on QOL have been reported in several studies [3][4][5]. Approximately one-third of women with breast cancer experience a psychological burden, including depressive mood [6].…”
mentioning
confidence: 99%
“…In the last-mentioned study physical complications were more evident in the older group of patients, while younger survivors had more psychological problems. Also, QOL may be related to the disease status and the number of chemotherapy cycles patients are prescribed [8], functional status as judged by the Karnofsky index [21] or pain [37]. One of the major shortcomings of past studies, however, is that the samples were made up mainly of women with advanced disease.…”
Section: Introductionmentioning
confidence: 99%